(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
It is not an exaggeration, that women in India are backbone of agriculture. They make fruitful economic contribution in the agriculture and rural economy. The female participation in agricultural activities varies with the land owning status of farm households. In this paper an attempt is made to analyze the participation of female in agriculture at the micro level by taking – tehsil as a unit of study. In this area most of work on farm is done by the female. In this paper an attempt is made to analyze the participation of female in agriculture at the micro level by taking – tehsil as a unit of study. In this area most of work on farm is done by the female. Women between the age group 15 to 60 years illiterate to women having education upto 10th were found to be engaged in agriculture. Their status is low mostly due to their limited access to economic resources. One way of bringing about an improvement in the status of the female workers is to raise the wages of the women workers to improve their economic condition.